Предмет: Алгебра, автор: alenakoval2004

Срочно.Помогите решить!

Приложения:

Ответы

Автор ответа: 4ibis88
1

(x-40)/39+(x-39)/40=39/(x-40)+40/(x-39)


[40(x-40)]/(39*40)+[39(x-39)]/(39*40)=

=[39(x-39)]/[(x-40)(x-39)]+[40(x-40)]/[(x-40)(x-39)]


[40(x-40)+39(x-39)]/(39*40)=

=[39(x-39)+40(x-40)]/[(x-40)(x-39)]


1/(39*40)=1/[(x-40)(x-39)]


[(x-40)(x-39)]=39*40


x^2-39x-40x+39*40=39*40


x^2-79x=0

x(x-79)=0

x=0 или x=79



Похожие вопросы
Предмет: Математика, автор: TikTasd
Предмет: Алгебра, автор: lalkinaksenia